A concise review on factors influencing the hematopoietic stem cell transplantation main outcomes. Issue 2 (7th May 2021) - Rafiee, Mohammad; Abbasi, Mohammad; Rafieemehr, Hassan; Mirzaeian, Amin; Barzegar, Mohieddin; Amiri, Vahid; Shahsavan, Shaghayegh; Mohammadi, Mohammad Hossein
Abstract: Background and aims: As a curative procedure, hematopoietic stemcell transplantation (HSCT) is an approved treatment for many malignant orbenign hematologic and non‐hematologic diseases. There are different outcomes of HSCT, as well as several parameters influencing these outcomes. Methods: We had searched scientific sources like Web ofScience and PubMed with a combination of keywords such as HSCT, engraftment, survival, outcomes, etc. Totally, 80 articles were included. Results: Here we have reviewed the effective factors onmain outcomes of HSCT including engraftment, survival, graft versus hostdisease, and Mobilization. Also, the prediction of hematological reconstitutionand some novel suggestions leading to better outcomes are reviewed. Conclusion: The study will be applicable for improvedmanagement of autologous and allogeneic HSCT process to increase the procedureefficiency.